2018
DOI: 10.1136/jim-2018-000786
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma Mansoni Antigen Sm-p80: Prophylactic Efficacy using TLR4 Agonist Vaccine Adjuvant Glucopyranosyl Lipid A-Alum in Murine and Non-Human Primate Models

Abstract: Sm-p80, the large subunit of calpain, is a leading candidate for a schistosomiasis vaccine. The prophylactic and antifecundity efficacy of Sm-p80 has been tested in three animal models (mouse, hamster and baboon) using a multitude of vaccine formulations and approaches. In our continual effort to enhance the vaccine efficacy, in this study, we have utilized the adjuvant, synthetic hexa-acylated lipid A derivative, glucopyranosyl lipid A (GLA) formulated in aluminum (GLA-Alum) with recombinant Sm-p80. The rSm-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
(101 reference statements)
2
14
0
5
Order By: Relevance
“…The rSm-p80 + GLA-Alum immunization regimen provided worm burden reduction by 33.33–53.13% and 38% in vaccinated mice and baboons, respectively. Strong Sm-p80 specific IgG, IgG1, IgG2a and IgM and a mix of TH cells response were observed in all immunized animals ( Zhang et al, 2018 ).…”
Section: Current Status Of Protein Vaccine Candidates Against mentioning
confidence: 95%
“…The rSm-p80 + GLA-Alum immunization regimen provided worm burden reduction by 33.33–53.13% and 38% in vaccinated mice and baboons, respectively. Strong Sm-p80 specific IgG, IgG1, IgG2a and IgM and a mix of TH cells response were observed in all immunized animals ( Zhang et al, 2018 ).…”
Section: Current Status Of Protein Vaccine Candidates Against mentioning
confidence: 95%
“…Immunomodulation is usually defined as modulation of the immune system, and this can be done by any chemical agent that modifies the immune response or the functioning of the immune system via the stimulation of antibody formation or the inhibition of white blood cell activity [93]. Cordycepin has been reported to stimulate cytokine release of resting peripheral blood mononuclear cells (PBMCs) as well as influence PBMCs proliferation and transcription factors in a human acute monocytic leukemia cell line (THP-1).…”
Section: Cordycepin and Immunomodulatory Effectsmentioning
confidence: 99%
“…Several studies have demonstrated that IL-21 is induced at both the mRNA and protein levels during natural infections with several species of schistosomes in humans and in murine models of schistosomiasis (Milner et al, 2010; Bourke et al, 2013; Zhang Y. et al, 2016), as well as following vaccination with schistosome-derived peptides (Zhang et al, 2013, 2018; Bourke et al, 2014; Fairfax et al, 2015). Ileal lamina propria lymphocytes-(LPLs) and axillary lymph node-derived T cells and non-T cell subsets from uninfected rhesus macaques ( Macaca mulatta ) secreted high levels of IL-21 in a recall assay in response to S. mansoni (Sm) egg antigen (SmEA) and worm antigen (SmWA) preparations ex vivo (Torben et al, 2017).…”
Section: Helminth Parasitesmentioning
confidence: 99%